Leading Sectors that Drive the Economy of Bali during the COVID-19 Pandemic - Ni Putu Wiwin Setyari; Anak Agung Bagus Putu Widanta; I Made Bram Sarjana; Anak Agung Alit Candra Gupta (Pusat Kajian Bali Universitas Udayana, 2022)
Due to the COVID-19 pandemic, the economy of Indonesia has weakened and contracted, although currently, the economy has recovered from it. The economy of Bali has experienced its lowest growth of all time. This is due to the huge impact of the COVID-19 pandemic on tourism in Bali, which is its economic locomotive. This research aims to analyze the potential sectors that can be developed by each regency and city in Bali to boost its economic recovery. The research used the LQ and overlay methods. The results of the research show that the sectors directly related to tourism have experienced contraction. Meanwhile, the sector that has progressed considerably and becomes a leading one during the current pandemic is the primary sector. Therefore, the Government of Bali needs to carry out an economic structural transformation, so that the economy will be stabilized and emerge stronger against various internal and external shocks.